Evaluasi Penerimaan Pengguna Sistem Informasi Kesehatan Pada Poliklinik Universitas Brawijaya Menggunakan Model Unified Theory of Acceptance and Use of Technology (UTAUT) - Vikry Aghnas Saharja; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This research aims to determine the level of acceptance of users of health information systems at the UB Polyclinic. This research was conducted using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This research was conducted by distributing questionnaires using 34 respondents' data using purposive sampling. Data collection is done by distributing questionnaires to users of health information systems. Furthermore, the data were analyzed using descriptive statistical analysis. The results of the descriptive analysis on the performance expectancy variables are in the very high category (89.7%), effort expectancy is in the very high category (86.9%), social influences fall into the high category (78.97%), while facilitating conditions enter in the very high category (80.29%). Based on the values obtained by the social influence variable and Facilitating conditions, it is a priority to be given recommendations for improvement